2018
DOI: 10.1002/ijc.31381
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide profiling of normal gastric mucosa identifies Helicobacter pylori‐ and cancer‐associated DNA methylome changes

Abstract: The large geographic variations in the incidence of gastric cancer (GC) are likely due to differential environmental exposures, in particular to Helicobacter pylori (H. pylori) infection. We aimed to investigate the impact of H. pylori on the epigenome in normal gastric mucosa and methylation changes associated with cancer risk independent of H. pylori. A discovery set of normal gastric mucosa from GC cases (n = 42) and controls (n = 42), nested in a large case-control study and stratified by H. pylori status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…The relationship between HP infection and gastric carcinogenesis has been substantially demonstrated. The carcinogenicity of HP has been well established, involving the injection of CagA by type IV secretion systems [4][5][6][7] or alterations to the DNA methylome [8][9][10][11]. Importantly, several prospective studies had stated that gastric cancer develops only in patients with HP infection [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between HP infection and gastric carcinogenesis has been substantially demonstrated. The carcinogenicity of HP has been well established, involving the injection of CagA by type IV secretion systems [4][5][6][7] or alterations to the DNA methylome [8][9][10][11]. Importantly, several prospective studies had stated that gastric cancer develops only in patients with HP infection [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Following the frequent inclusion of epigenetics as a parameter in environmental epidemiology studies, numerous reports have been made in recent years associating alterations in DNA methylation with various environmental factors, including biological agents, dietary habits, and air pollution (Ambatipudi et al 2016;Barouki et al 2018;de FC Lichtenfels et al 2018;Degli Esposti et al 2017;Fasanelli et al 2019;Feil and Fraga 2012;Hattori and Ushijima 2016;Herceg et al 2018;Martin and Fry 2018;Perrier et al 2019;Woo et al 2018). Similarly, many reports indicate that microRNA (miRNA) profiles are responsive to various environmental exposures, including air pollution ; Espín-Pérez et al (2018), both epidemiological studies], nanoparticles [Brzóska et al (2019), utilizing human liver cells], endocrine disruptors, such as bisphenol A (BPA) [Chou et al (2017), using human endometrial cells, and Martínez-Ibarra et al (2019), using human blood samples], and dichlorodiphenyltrichloroethane (DDT) [Krauskopf et al (2017), using human blood]. Long noncoding RNAs (lncRNAs), although still a relatively new area of research, have been reported to be associated with levels of phthalates in first trimester urine of pregnant women (LaRocca et al 2014), benzene in seven exposed individuals (Bai et al 2014b), and occupational exposure to cadmium (Zhou et al 2015) and to be responsive to developmental exposure to BPA in mice (Kumamoto and Oshio 2013) and to certain heavy metals in in vitro (Tani et al 2014;Zhou et al 2015) and in vivo experimental systems (Zhou et al 2015).…”
Section: Environmental Toxicants As Disruptors Of Epigenetic Regulationmentioning
confidence: 99%
“…The HP status was determined via Wright-Giemsa staining of the biopsy specimens by a pathologist who specialized in GC. A current infection was defined as at least one positive test result in the rapid urease test or histological evaluation of four biopsy sites [62]. Participants were asked to complete a self-administered questionnaire.…”
Section: Data Collectionmentioning
confidence: 99%